Efficient Cisplatin Pro‐Drug Delivery Visualized with Sub‐100 nm Resolution: Interfacing Engineered Thermosensitive Magnetomicelles with a Living System. Issue 7 (6th June 2014) - Vitol, Elina A.; Rozhkova, Elena A.; Rose, Volker; Stripe, Benjamin D.; Young, Natalie R.; Cohen, Ezra E. W.; Leoni, Lara; Novosad, Valentyn
<x xml:space="preserve">Abstract</x> Temperature‐responsive magnetic nanomicelles can serve as thermal energy and cargo carriers with controlled drug release functionality. In view of their potential biomedical applications, understanding the modes of interaction between nanomaterials and living systems and evaluation of efficiency of cargo delivery is of the utmost importance. In this work, we investigate the interaction between the hybrid magnetic nanomicelles engineered for controlled platinum complex drug delivery and a biological system at three fundamental levels: subcellular compartments, a single cell and whole living animal. Nanomicelles with polymeric P(NIPAAm‐co‐AAm)‐b‐PCL core‐shell were loaded with a hydrophobic Pt(IV) complex and Fe3O4 nanoparticles though self‐assembly. The distribution of a platinum complex on subcellular level is visualized using hard X‐ray fluorescence microscopy with unprecedented level of detail at sub‐100 nm spatial resolution. We then study the cytotoxic effects of platinum complex‐loaded micelles in vitro on a head and neck cancer cell culture model SQ20B. Finally, by employing the magnetic functionality of the micelles and additionally loading them with a near infrared fluorescent dye, we magnetically target them to a tumor site in a live animal xenografted model which allows to visualize their biodistribution in vivo.